Emotion Regulation in Women with PTSD and Addiction - Tajeryan, Zeynab; Afrooz, Gholam Ali; Nouryghasemabadi, Robabeh (Psychology of Woman Journal, 2023)
Objective: In this study, emotion regulation between two groups of women with PTSD, one group with addiction and one without, was examined.Methods and Materials: The sample size consisted of 179 individuals, including 56 individuals with PTSD without a history of addiction, 51 individuals with PTSD and addiction, 39 individuals with addiction, and 33 individuals from the general population. The tools used in the research were the Post-Traumatic Stress Disorder Checklist (PCL-5) and the Cognitive Emotion Regulation Questionnaire (CERQ).Findings: The results of the multivariate analysis of variance for positive and negative emotion regulation and their subscales indicated a significant difference between the addicted and non-addicted groups.Conclusion: The findings showed that when PTSD symptoms are checked over a longer period and the individual is not addicted, there are more problems in negative emotion regulation. Conversely, when PTSD is checked over a longer period but the individual is addicted, lower scores are obtained in positive emotion regulation.